How Social Media can be used to promote Catholic Social Teaching: A Lebanese Case Study - Fahed, Ziad; Saliba, Marie Belle (Revista Pistis & Praxis, 2021)
Since the emergence of social media websites and applications, researchers have been intrigued by the fast attraction of these platforms of millions of users worldwide. From Instagram to Tiktok and Reddit, social media platforms are connecting people from all around the globe. Many articles examined the relation between social media and the church, how this type of media could affect the church and whether the use of social media would impact the growth of the church or not. However, few articles tackled the relationship between social media and Catholic Social Teaching (CST). Thus, this article aims at analyzing the different aspects of the bonds that tie social media to Catholic Social Teaching. It pinpoints the positive impact social media have on the promotion of CST as well as the challenges and limitations that might come along using these platforms. It also uses the specific case of Lebanon to highlight the ways social media could be used to promote the common good.